Data hiding using bit plane complexity segmentation steganography - Chandra Sekhar, M; K. Chandini, S; Sai Rohith, V; Jhansi Lakshmi, V; Pavan Kumar, M (International Journal of Engineering and Technology, 2018)
Steganography is the basis of information covering the puzzle in some other data (we call it the ship), leaving no obvious evidence of data change. Most conventional steganographic strategies is limited data that hide the limit. They can cover up just 10% (or less) of the information measures of the vessel. This is on the grounds that the standard of those procedures was either to supplant an uncommon piece of the recurrence parts of the vessel picture, or to supplant all the slightest critical image bits with a secret multi-valued data. Our new Steganography uses the image as vessel information, and we enter the data in the bit-plane mystery vessel. This strategy makes use of human attributes, through which people cannot see the structure of any form of data exclusively damned pair, for example. We can replace most of the Â«Commotion like" regions in the bit-planes of the puzzle vessel image data without deteriorating the quality of the photos. We called our steganography "BPCS-steganography," which remains a Bit-Plane Complexity Segmentation steganography.Â Â